A Comprehensive Analysis of Stock Index Connectedness and Volatility Spillovers Between Colombia, Brazil, Mexico, Chile, and the United States - Juan Manuel Candelo-Viáfara; María del Pilar Rivera-Díaz; Juan Esteban Orrego-Reyes (Revista CEA)
Objective: This paper examines the interconnectedness of stock market indices between the United States and four Latin American countries: Colombia, Brazil, Mexico, and Chile. Particularly, it focuses on linkages and spillover effects, analyzing both the tails and the mean of the distribution. Design/Methodology: To address this gap identified in the literature, this study investigates the pre- and post-COVID-19 periods using the Quantile Vector Autoregression (QVAR) approach. Findings: The analysis revealed significant time variations in co-movements between stock indices, with notable peaks during the 2014–2017 and 2020–2021 periods. These peaks correspond to OPEC’s strategic shift in oil production and the global COVID-19 pandemic. Connectedness levels above 50 % underscore a high degree of interdependence, with the strongest connectedness observed in extreme quantiles, which signals increased risks during critical market conditions. Conclusions: This study identified significant volatility interconnectedness among U.S. and Latin American stock indices, with peaks during major global events such as OPEC’s 2014 strategy shift and the COVID-19 pandemic. Brazil emerges as a key driver of regional volatility transmission. Analysis of extreme quantiles revealed heightened spillovers during turbulent periods, underscoring increased market risk. These findings emphasize the impact of geopolitical and economic factors on market dynamics and offer valuable insights for investors, risk managers, and policymakers to navigate periods of elevated market uncertainty. Originality: These findings highlight pronounced volatility spillovers in the extreme tails of the distribution, accentuating increased uncertainty and risks associated with significant market fluctuations.